2005
DOI: 10.1007/s10531-004-7844-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed banks of two montane riparian areas: implications for restoration

Abstract: Understanding the role of seed banks can be important for designing restoration projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
5
33
0
Order By: Relevance
“…When we compared our results with those obtained by other authors (Gunther et al 1984;Schneider & Sharitz 1986;McGraw 1987;Titus 1988;Goodson et al 2002;Nicol et al 2003;Leck & Schütz 2005;Richter & Stromberg 2005), we found that the species richness of the seed bank in the secondary forest we studied here was high (53 species), particularly in broadleaf herbaceous life forms. Our seed bank also showed a high estimated seed density (3603 seeds/ m 2 ), not only due to the herbaceous species but also due to trees.…”
Section: Discussionsupporting
confidence: 70%
“…When we compared our results with those obtained by other authors (Gunther et al 1984;Schneider & Sharitz 1986;McGraw 1987;Titus 1988;Goodson et al 2002;Nicol et al 2003;Leck & Schütz 2005;Richter & Stromberg 2005), we found that the species richness of the seed bank in the secondary forest we studied here was high (53 species), particularly in broadleaf herbaceous life forms. Our seed bank also showed a high estimated seed density (3603 seeds/ m 2 ), not only due to the herbaceous species but also due to trees.…”
Section: Discussionsupporting
confidence: 70%
“…The role of soil seed bank to vegetation development following disturbance has been reported by numerous authors (Yamada et al 2007;Keddy et al 1989;Looney and Gibson 1995;Falińska 1999;Chambers 2000;Zabinski et al 2000;Bossuyt and Hermy 2001;Harwell and Havens 2003;Richter and Stromberg 2005;Lang and Halpern 2007;Lee et al 2008;Li et al 2008;Ma et al 2011Ma et al , 2013Savadogo et al 2017) because it often leads the initial vegetation trajectory and species composition in the course of secondary succession after disturbance. Richness and density of soil seed banks often decrease as vegetation passes through the stages of succession (Pickett and McDonnell 1989;Thompson 2000).…”
Section: Introductionmentioning
confidence: 93%
“…Consequently, they can germinate when the surrounding environment becomes appropriate for growth (Fenner 1985). Recently, studies on active restoration using seed banks and the potential contribution of seed banks for restoration have been gradually increasing (Augusto et al 2001, Richter and Stromberg 2005, Roovers et al 2006, Koh 2007, Lee 2007, Zhan et al 2007, Lee et al 2008.…”
Section: Comparison Of Vegetation Typesmentioning
confidence: 99%
“…Seed banks are very useful for recovery of annual plants after disturbances (Baskin and Baskin 1980, Lee et al 2008) and for the design of restoration projects (Richter and Stromberg 2005). Dormant seeds…”
Section: Restoration Of Salt Marshes Using Seed Banksmentioning
confidence: 99%